Polymer Additive Engineering of Organolead Halide Perovskites: Effect on Device Characteristics and Scalable Manufacturing - Mathur, Avi (University of Waterloo, 2022)
Within the last decade, organolead halide perovskites such as methylammonium lead iodide (MAPbI₃), have established themselves as a promising material choice for developing highly efficient and cost-effective photosensitive devices ranging from solar cells to photodetectors, display devices, light-emitting diodes (LEDs), self-powered devices, sensors and beyond. Despite exhibiting impeccable electro-optical properties and ease of solution processibility, the instability of perovskite under an ambient atmosphere hinders their commercial viability. The key issue lies in the degradation of the perovskite material in presence of light, O₂, moisture, and high temperature, along with the migration of the constituent ions (especially MA⁺ and I⁻ owing to their low activation energy) under an electrical field. In addition to abundant gases such as oxygen, nitrogen, and carbon dioxide, the interaction with omnipresent gas such as carbon monoxide (CO) at the perovskite interface can critically affect the electro-optical and mechanical properties and stability of the resultant perovskite devices. It is observed that exposure to the CO environment can displace adsorbed O₂ and leads to a lowering of work function and induces self-doping in the MAPbI₃ film. Interaction with CO at the perovskite film interface leads to layer-by-layer depletion of the organic moiety leaving behind PbI₂ and this also softens the film over time. While long-duration exposure is detrimental to the electro-optical properties of the perovskite film, short exposure to the CO causes a 122% enhancement in the self-powered capacity of these films, which has significant implications for their applications in photodetectors, electrochemical cells, and sensors. To address these instability issues, several strategies are being actively researched. These involve compositional engineering, the addition of interfacial layers, encapsulation of the entire device, or a combination of multiple of these. These strategies however mandate additional resources, and an inert atmosphere and may lead to an undesirable blue shift of the absorption spectrum hampering the feasibility of the device fabrication. Further, these fail at alleviating the internal degradation of perovskite caused by ion migration. The stability issues in perovskites can be instead addressed by material engineering strategy, based on the specific chemical interaction of polymer additive with the perovskite precursors. Inspired by the direct interaction between organic molecules and inorganic moieties in biological and bio-inspired systems where the addition of organic molecules (primarily amino acids, DNA, and RNA) may alter the crystallization kinetics, and crystal phase switching & orientation, morphology, and other structural properties of the inorganic-organic composite, lead iodide (PbI₂) facilitated in-situ cross-linking of PS chains in the perovskite precursor solution, is presented. The cation-π interaction between the MA⁺ and long-order PS molecules at the grain boundaries and at interfaces facilitates the formation of a three-dimensional molecular network in the MAPbI₃ film with uniform morphology, enhanced grain size, mobility, and carrier lifetime with reduced ion migration, charge recombination, and dark currents. Different polymer additives may inherently differ not only in terms of their affinity for water and conductivity but also in the interaction mechanism with the perovskite precursors owing to the difference in polarity. Hence, to understand which characteristics of the polymer might be more important for achieving stable perovskite-polymer composite films without compromising the device performance, the strong interaction capabilities of the hydrophilic polar polyethylene glycol (PEG) and hydrophobic non-polar PS polymers in a PEG-PS block co-polymer system have been utilized. Such an approach provides a better understanding of the effective contribution of each polymer counterpart when mixed alongside perovskite precursors. It is realized that while the presence of PS enhances the average grain size, the presence of merely PEG as an additive leads to enhanced heterogeneous nucleation which increases the density of grain boundaries and trap sites within the perovskite films and proves insufficient to reduce ionic conductivity. Further, the fabrication of ambient atmosphere stable perovskite films mandates the presence of hydrophobic PS chains. It is observed that the integration of PS chains with organolead halide perovskite films, leading to enhanced stability and electro-optical performance, is critically affected by the molecular weight of chains. The molecular weight determines the mobility and volume of the chains, which affects the crystallization kinetics and, hence, perovskite grain size. The insulating nature of the PS chains is another critical factor that affects both ion migration and the conduction of electronic charges. The combined effect of these factors leads to optimal performance with the use of medium-length chains. A simple model integrating the two effects accurately fits the response of the polymer–perovskite composite. Further characterization results show that the polymer–perovskite films have a three-layer architecture consisting of nanoscale polymer-rich top and bottom layers. These combined results show that the optimization of performance in polymer–perovskite devices depends critically on the size of the chains due to their multiple effects on the perovskite matrix. The rigid and brittle nature of MAPbI₃ polycrystalline films limits their application in stretchable devices due to rapid deterioration in performance on mechanical cycling. By incorporation of PS chains in the MAPbI₃ films, the mechanical modulus and the viscoelastic nature of the films are altered. Combining this with flexible nanochain electrodes, highly stretchable and stable perovskite devices have been fabricated. The resultant PS-MAPbI₃ photodetector exhibits ultralow dark currents (∼10⁻¹¹ A) and high light switching ratios (∼10³) and maintains 75% of performance after 30 days. The viscoelastic nature and lower modulus of the polymer improve the energy dissipation in the polymer-MAPbI₃ devices; as a result, they maintain 52% of the device performance after 10000 stretching cycles at 50% strain. The difference in the mechanical behavior is observed in the failure mode of the two films. While rapid catastrophic cracking is observed in MAPbI₃ films, the intensity and size of such crack formation are highly limited in polymer-MAPbI₃ films, which prevents their failure. The PS integration strategy provides a route for scalable manufacturing of perovskite films by utilizing the room-temperature blade coating technique. This serves the dual purpose of addressing the challenges of developing large area perovskite film-based devices which can survive in the ambient atmosphere without compromising on efficiency. It can thus pave the way for the cost-effective commercialization of perovskite-based electro-optical devices with a larger active area. Overall, the findings of this research work highlight the ability to tune the characteristics of the perovskite-based photosensitive device and extend them beyond rigid substrates to realize stretchable devices by a single-step method of integrating a commodity scale polymer in the perovskite films. This work also provides a deep insight into the improved stability and architecture of perovskite-polymer hybrid films which will be of significant interest to the research community. Such a facile polymer additive strategy combined with an ambient atmosphere compatible blade coating technique will pave the way for the development of polymer-perovskite hybrid assembly for long-term device applications and their scalable manufacturing.
Keywords: perovskites; halide perovskites; polymer additive; copolymer; defect passivation; additive engineering; polystyrene; methylammonium lead iodide; perovskite-polymer; self-powered; photodetector; energy harvesting; molecular weight; polymer mobility; carbon monoxide; flexible electrode; stretchable; optoelectronic devices; solar cells; long-term stability; ambient atmosphere stability; large-area solar cells